Comparing the use of direct observation, standardized patients and exit interviews in low- and middle-income countries: a systematic review of methods of assessing quality of primary care. Issue 3 (12th December 2020) - Aujla, Navneet; Chen, Yen-Fu; Samarakoon, Yasara; Wilson, Anna; Grolmusová, Natalia; Ayorinde, Abimbola; Hofer, Timothy P; Griffiths, Frances; Brown, Celia; Gill, Paramjit; Mallen, Christian; Sartori, Jo; et al.
Abstract: Clinical records in primary healthcare settings in low- and middle-income countries (LMIC) are often lacking or of too poor quality to accurately assess what happens during the patient consultation. We examined the most common methods for assessing healthcare workers' clinical behaviour: direct observation, standardized patients and patient/healthcare worker exit interview. The comparative feasibility, acceptability, reliability, validity and practicalities of using these methods in this setting are unclear. We systematically review and synthesize the evidence to compare and contrast the advantages and disadvantages of each method. We include studies in LMICs where methods have been directly compared and systematic and narrative reviews of each method. We searched several electronic databases and focused on real-life (not educational) primary healthcare encounters. The most recent update to the search for direct comparison studies was November 2019. We updated the search for systematic and narrative reviews on the standardized patient method in March 2020 and expanded it to all methods. Search strategies combined indexed terms and keywords. We searched reference lists of eligible articles and sourced additional references from relevant review articles. Titles and abstracts were independently screened by two reviewers and discrepancies resolved through discussion. Data were iteratively coded according to pre-defined categories and synthesized. We included 13 direct comparison studies and eight systematic and narrative reviews. We found that no method was clearly superior to the others—each has pros and cons and may assess different aspects of quality of care provision by healthcare workers. All methods require careful preparation, though the exact domain of quality assessed and ethics and selection and training of personnel are nuanced and the methods were subject to different biases. The differential strengths suggest that individual methods should be used strategically based on the research question or in combination for comprehensive global assessments of quality.